Bypassing the Need for the Transcriptional Activator EarA through a Spontaneous Deletion in the BRE Portion of the fla Operon Promoter in Methanococcus maripaludis - Ding, Yan; Berezuk, Alison; Khursigara, Cezar M.; Jarrell, Ken F. (Frontiers in Microbiology, 2017)
In Methanococcus maripaludis, the euryarchaeal archaellum regulator A (EarA) is required for the transcription of the fla operon, which is comprised of a series of genes which encode most of the proteins needed for the formation of the archaeal swimming organelle, the archaellum. In mutants deleted for earA (∆earA), there is almost undetectable transcription of the fla operon, Fla proteins are not synthesized and the cells are non-archaellated. In this study, we have isolated a spontaneous mutant of a ∆earA mutant in which the restoration of the transcription and translation of the fla operon (using flaB2, the second gene of the operon, as a reporter), archaella formation and swarming motility were all restored even in the absence of EarA. Analysis of the DNA sequence from the fla promoter of this spontaneous mutant revealed a deletion of three adenines within a string of seven adenines in the transcription factor B recognition element (BRE). When the three adenine deletion in the BRE was regenerated in a stock culture of the ∆earA mutant, very similar phenotypes to that of the spontaneous mutant were observed. Deletion of the three adenines in the fla promoter BRE resulted in the mutant BRE having high sequence identity to BREs from promoters that have strong basal transcription level in Mc. maripaludis and Methanocaldococcus jannaschii. These data suggest that EarA helps recruit transcription factor B to a weak BRE in the fla promoter of wildtype cells but is not required for transcription from the fla promoter with a strong BRE, as in the three adenine deletion version in the spontaneous mutant.